2014
DOI: 10.1007/s13105-014-0359-7
|View full text |Cite
|
Sign up to set email alerts
|

Cypermethrin alters the status of oxidative stress in the peripheral blood: relevance to Parkinsonism

Abstract: Parkinson's disease (PD) is a motor scarcity disorder characterized by the striatal dopamine deficiency owing to the selective degeneration of the nigrostriatal dopaminergic neurons. While oxidative stress is implicated in PD, prolonged exposure to moderate dose of cypermethrin induces Parkinsonism. The study aimed to investigate the status of oxidative stress indicators and antioxidant defence system of the polymorphonuclear leukocytes (PMNs), platelets and plasma to delineate the effect of Parkinsonian dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…The finding that the highly exposed group of workers had lower CD4/CD8 as compared to the unexposed group was in agreement with a cross-sectional study of CYP occupational exposures, which found that exposed workers had lower level of CD4% and CD4/CD8% as compared to other less or not exposed groups [21]. Although the reference range for normal value was not exceeded in both studies but the possibility of immune system imbalance diseases as Parkinsonism as a result of oxidative stress caused by CYP exposure [27]. The current study investigated the effect of socio-demographic and occupational factors on oxidative stress, genotoxicity and immunological disturbances among exposed workers.…”
Section: Ijomeh 2017;30(4)supporting
confidence: 88%
“…The finding that the highly exposed group of workers had lower CD4/CD8 as compared to the unexposed group was in agreement with a cross-sectional study of CYP occupational exposures, which found that exposed workers had lower level of CD4% and CD4/CD8% as compared to other less or not exposed groups [21]. Although the reference range for normal value was not exceeded in both studies but the possibility of immune system imbalance diseases as Parkinsonism as a result of oxidative stress caused by CYP exposure [27]. The current study investigated the effect of socio-demographic and occupational factors on oxidative stress, genotoxicity and immunological disturbances among exposed workers.…”
Section: Ijomeh 2017;30(4)supporting
confidence: 88%
“…Oxidative stress has been a matter of concern in the pathogenesis of neurodegenerative diseases (Patel et al, 2006;Gupta et al, 2010). Recently, Tripathi et al (2014) showed that the pyrethroid cypermethrin decreased the striatal dopamine content by altering the status of oxidative stress indicators and antioxidant defense system; this mechanism of oxidative stress might be of value for predicting the nigrostriatal dopaminergic neurodegeneration and the nigrostriatal toxicity related to neurological disorders (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al (19) identified higher nitrite (an indicator of nitrosamine stress) and lipid peroxide (LPO, an indicator of oxidative stress) levels in the nigrostriatum. Nitrite and LPO were also significantly increased in the peripheral blood of rats exposed to cypermethrin dose that induces nigrostriatal dopaminergic neurodegeneration (26).…”
Section: Pyrethroidsmentioning
confidence: 93%